Ethnicisation and Identity Construction in Malaysia by Frederik Holst, Routledge, 2012, 256pp. - Mustafa K Anuar (Kajian Malaysia, 2013)
The diverse nature of multicultural, multiethnic and multi-religious Malaysia, and its accompanying socio-cultural and political challenges, attracts the curiosity and, subsequently, prompts academic investigation of many researchers from within and outside the country to interrogate particularly issues of ethnicity, identities and politics.